(untitled) (Journal of Computational Intelligence and Robotics, 2023)
The growing complexity of modern IT systems necessitates innovative approaches to workflow automation, especially in Platform-as-a-Service (PaaS) architectures. This research focuses on the chaining of artificial intelligence (AI) agents, including task-specific models, large language models (LLMs), and decision-making algorithms, to facilitate the automation of multi-step workflows in cloud-native environments. By leveraging frameworks such as LangChain, the integration of heterogeneous AI agents into cohesive multi-agent systems becomes feasible, enabling the decomposition and resolution of intricate tasks across various domains. The paper elaborates on the architectural design principles, interoperability challenges, and optimization techniques involved in chaining AI agents within PaaS ecosystems. Specifically, it explores methods for orchestrating AI agents to achieve modularity, scalability, and fault tolerance, which are critical for supporting dynamic and distributed workflows. A key focus is on how AI-driven orchestration tools ensure efficient task allocation and execution by dynamically selecting and connecting relevant agents based on task-specific requirements. The discussion extends to cloud-native implementation strategies, emphasizing containerization, microservices, and the use of serverless architectures to deploy AI agents as scalable components. By adopting event-driven architectures, these multi-agent systems can efficiently respond to workflow triggers, minimizing latency and maximizing throughput. Additionally, advanced techniques such as reinforcement learning and contextual reasoning are employed to enable agents to adapt their behavior based on real-time data, ensuring robust and context-aware decision-making. Real-world applications are demonstrated through case studies, with a particular focus on IT incident response workflows. These examples illustrate how chaining AI agents can expedite root cause analysis, generate automated remediation steps, and improve overall system reliability. The case studies also highlight the integration of LLMs for natural language understanding and communication, enabling seamless human-agent collaboration. Moreover, this paper critically examines the limitations and challenges of deploying such systems, including data security, agent communication bottlenecks, and the computational overhead of managing large-scale AI agent ecosystems. Strategies to mitigate these challenges are proposed, such as adopting privacy-preserving techniques like secure multi-party computation and improving inter-agent communication protocols using lightweight serialization methods. The paper concludes with a discussion on future directions, including advancements in federated learning for secure data sharing among AI agents, the role of autonomous agents in edge computing, and the potential of AI chains to transform industries beyond IT, such as healthcare, finance, and manufacturing. By providing a comprehensive framework for chaining AI agents in PaaS architectures, this research contributes to the field of automated workflow management and paves the way for more resilient, scalable, and intelligent multi-agent systems.